Separation of Ternary Mixtures by Pseudo-Simulated Moving-Bed Chromatography: Separation Region Analysis - Nuno S. Graça (2015)
The application of the pseudo-simulated moving bed process, known as JO process of Japan Organo Co., to the separation of ternary mixtures was studied. In order to perform a desired separation, the choice of the different operation parameters such as the duration of each step and its respective flow rates requires the use of a methodology that could provide the best process performance. This issue is addressed by proposing an innovative method to determine the JO operation region, which establishes the operation limits of the process. In addition, a methodology is presented to determine the separation region where a minimum purity requirement is guaranteed. This methodology was applied to a ternary mixture considering linear adsorption isotherms. It was possible to construct a separation region for minimum purity of 99.9% in all the outlet streams and identify the best operation point in terms of the process performance.